Major Publications in the Critical Care Pharmacotherapy Literature: 2020. (9th December 2021) - Bissell, Brittany D.; Campbell, Jeannee; Collins, Reagan; Cook, Charles; Desai, Dharati; DeWitt, Jessica; Eche, Ifeoma Mary; Eche, Ijeoma Julie; Elsamadisi, Pansy; Juul, Janelle; Kim, Soyoung; Makowski, Courtney T.; et al.
Abstract : OBJECTIVES: To summarize selected meta-analyses and trials related to critical care pharmacotherapy published in 2020. DATA SOURCES: The Clinical Pharmacy and Pharmacology Pharmacotherapy Literature Update group screened 36 journals monthly for impactful publications. STUDY SELECTION: The group reviewed a total of 119 articles during 2020 according to relevance for practice. DATA EXTRACTION: Articles were selected with consensus and importance to clinical practice from those included in the monthly Clinical Pharmacy and Pharmacology Pharmacotherapy Literature Update. The group reviewed articles according to Grading of Recommendations, Assessment, Development, and Evaluations criteria. Articles with a 1A grade were selected. DATA SYNTHESIS: Several trials were summarized, including two meta-analyses and five original research trials. Original research trials evaluating vitamin C, hydrocortisone, and thiamine versus hydrocortisone in sepsis, the use of nonsedation strategies, dexmedetomidine in cardiac surgery, remdesivir for severe acute respiratory syndrome coronavirus 2, and thrombectomy in acute ischemic stroke. Two meta-analyses determining the impact of norepinephrine initiation in patients with septic shock and the use of corticosteroids in severe acute respiratory syndrome coronavirus 2 was included. CONCLUSIONS: This clinical review provides summary and perspectives of clinical practice impact on influential critical care pharmacotherapy publications in 2020.